(untitled) (International Seven Journal of Health Research, 2023)
In the context of outpatient dental care, especially during surgical and invasive procedures involving the topical application of anesthesia, it is essential to carry out prior complementary and laboratory tests to assess the patient’s general state of health before the intervention. These tests play a crucial role in the early diagnosis of systemic diseases and in monitoring these conditions, with the aim of controlling them to avoid interfering with dental treatment. This study highlights the importance of various complementary exams in dental practice, offering clear and objective guidelines to the dental surgeon on the interpretation of results, the appropriate ordering of exams and the proper management of the patient.